Ultrashort echo time time‐spatial labeling inversion pulse magnetic resonance angiography with denoising deep learning reconstruction for the assessment of abdominal visceral arteries. Issue 6 (26th December 2020) - Mori, Ryuichi; Kassai, Yoshimori; Masuda, Atsuro; Morita, Yoshiaki; Kimura, Tomoyoshi; Nagasaka, Tatsuo; Nishina, Takashi; Tanaka, Sho; Miyazaki, Mitsue; Takase, Kei; Ota, Hideki
Abstract: Current contrast‐enhanced magnetic resonance angiography (MRA) and non‐contrast‐enhanced balanced steady‐state free precession (bSSFP) MRA cause susceptibility artifacts from metallic devices in assessing endovascular visceral‐artery interventions. The aims of this study are to investigate and compare image quality (IQ) and susceptibility artifacts of three‐dimensional (3D) ultrashort echo time (UTE) time‐spatial labeling inversion pulse (Time‐SLIP) with those of 3D bSSFP Time‐SLIP and to assess denoising deep learning reconstruction (dDLR) for the improvement of the signal‐to‐noise ratio (SNR) in 3D UTE with sparse sampling in phantoms and human subjects. This is a prospective type of study. Pulsatile glycerin‐water flow phantom with platinum‐tungsten‐alloy coil, stainless‐steel, nitinol, and cobalt‐alloy stents were used. Ten healthy volunteers (seven males) and three patients (two males) were included in this study. 3D UTE Time‐SLIP and 3D bSSFP Time‐SLIP at 3T were used. The phantom‐based study compared the signal‐intensity ratio of the device levels (SRdevice ) and distal segments (SRdistal ) to the proximal segments. The volunteer‐based study measured SNR, contrast ratio (CR), and IQ. The patient study evaluated local artifacts from metallic devices. Statistical tests included paired t ‐tests, Wilcoxon‐signed rank tests, and Kruskal–Wallis tests. In the phantom‐based study, SRdevice was small with UTE Time‐SLIP, except the stainless‐steel stent. SRdistal was greater (49.1%–90.4%) on bSSFP images than UTE images (−11.1% to 9.6%). Among volunteers, dDLR in UTE images improved SNR ( p  < 0.05) and IQ ( p  < 0.05), but CR was unaffected. UTE Time‐SLIP showed inferior SNR and IQ than bSSFP Time‐SLIP in images with and without dDLR ( p  < 0.05 for each). However, among patients, UTE Time‐SLIP showed reduced metal artifacts compared to bSSFP Time‐SLIP. Irrespective of the lower SNR and IQ of 3D UTE Time‐SLIP than those of 3D bSSFP Time‐SLIP, the former appeared to better depict flow after stenting or coiling. This indicates the potential of 3D UTE Time‐SLIP to provide suitable diagnostic images of target vessels. dDLR improved SNR with reducing artifacts related to radial sampling, while maintaining the contrast. Level of Evidence: 2. Technical Efficacy Stage: 2.